LINGUISTIC SCHOOLS: UNLOCKING THE MYSTERIES OF LANGUAGE - Okhunjonov Akmaljon Shukhratovich (International Journal on Integrated Education, 2023)
Linguistic schools are theoretical frameworks and approaches that aim to understand and explain language and its structure. Each school emphasizes different aspects of language and employs varying methodologies. Linguistic schools encompass a range of theoretical viewpoints used to analyze and interpret language phenomena. Structuralism, one of the earliest schools, focuses on the structure and organization of language elements. It highlights the study of phonetics, phonology, morphology, syntax, and semantics. On the other hand, generative grammar examines the innate rules and principles that underlie language production and comprehension, proposing a formal system of grammar. Functional linguistics emphasizes the communicative and pragmatic aspects of language, aiming to uncover how language serves various social and cognitive functions. It investigates the relationship between language and its context.